Effect of Temperature and Duration Time of Maceration on Nitrate Content of Vernonia cinerea (L.) Less.: Circumscribed Central Composite Design and Method Validation - Chaowalit Monton; Chitradee Luprasong (International Journal of Food Science)
Vernonia cinerea (L.) Less. is a herbal plant in Family Asteraceae. It can be used as a smoking cessation aid due to the fact that it contains nitrate which can induce tongue numbness and cause less favor of cigarette smell and taste. The aim of this work was to investigate the effect of maceration temperature and time on the nitrate content of V. cinerea. A circumscribed central composite experimental design was applied in the work. Two factors (temperature and duration time) were investigated and two responses (yield of the extraction and nitrate content) were monitored. The high performance liquid chromatography using for quantitative analysis of nitrate content was validated. The HPLC response was linear (R2 = 1.000) in range of 10-100 μg/mL. The HPLC method was specific, precise, and accurate. The maceration temperature and time were varied from 40 to 100°C and 10 to 60 min, respectively. Results showed that maceration at high temperature and long duration time gave the simultaneous high yield of the extraction and nitrate content. The prediction by the computer software, Design-Expert, was stable, reliable, and accurate. The optimal condition that provided simultaneous high yield of the extraction and nitrate content was achieved when extraction was at 99.5°C for 56.4 min. V. cinerea extracted using the optimal condition gave the yield of the extraction and nitrate content of 15.6% and 0.610%, respectively. In conclusion, maceration temperature and duration time had a positive effect on yield of the extraction and nitrate content of V. cinerea. Furthermore, the optimal condition in this work could be used as a guide for extraction of V. cinerea to obtain the high yield of the extraction as well as nitrate content.